Career progression - the views of Queensland's nurses - Eley, R.; Francis, K.; Hegney, Desley (Australian Nursing Federation, 2013)
Objectives: To inform policy through determination of the views of Queensland nurses on career progression. Design: A quantitative cross-sectional cohort design with mailed survey. Setting: Financial members of the Queensland Nurses’ Union .Main outcome measures: Extent of the relationship between opportunity for career progression in nursing with turnover and retention. Results: A majority (54.4%) of the 1365 respondents were satisfied with their career progression. Only 11.6% were dissatisfied. Satisfaction was not related to length of time in nursing, but did increase among nurses enrolled in further education programs. Dissatisfaction was related to four themes: lack of support to advance knowledge; lack of opportunities for promotion; number of career options; and costs associated with advancement. A quarter of the nurses were contemplating a move within nursing in the next year and most of these nurses (62%) indicated that the move was for the purpose of career advancement. One in six nurses were contemplating leaving nursing altogether; however only 12.8% of those cited lack of career as the factor for intended departure. Results continued the trend seen in previous surveys over the last decade of a small but significant reduction in the perception that career prospects in nursing were limited. Conclusion: Although the perception that there are limitations to career advancement in nursing has reduced in the last decade, there is still room for improvement. Lack of career progression remains a concern of nurses; however this is not generally manifested in an intention to leave nursing. Rather, nurses are prepared to consider moves within nursing to further their careers.